2017
DOI: 10.1371/journal.pone.0179920
|View full text |Cite
|
Sign up to set email alerts
|

Unique intrahepatic transcriptomics profiles discriminate the clinical phases of a chronic HBV infection

Abstract: Chronic hepatitis B is a highly heterogeneous liver disease characterized by phases with fluctuations in viral replication and progressive liver damage in some, but not all infected individuals. Despite four decades of research, insight into host determinants underlying these distinct clinical phases—immunotolerant, immune active, inactive carrier, and HBeAg-negative hepatitis–remains elusive. We performed an in-depth transcriptome analysis of archived FFPE liver biopsies of each clinical phase to address host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…[15][16][17] We have recently shown that at the transcriptome level, B cell-related genes are expressed more in disease phases with elevated ALT, both in blood and livers of untreated patients with CHB, suggesting a direct or indirect involvement in the immunopathogenesis. 1,9 Here we applied fluorescently labeled HBcAg as baits to ex vivo track HBcAg-specific B cells in blood samples of a wellcharacterized cohort of patients with CHB. We also examined functional differences in B cell ELISPOT assays.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17] We have recently shown that at the transcriptome level, B cell-related genes are expressed more in disease phases with elevated ALT, both in blood and livers of untreated patients with CHB, suggesting a direct or indirect involvement in the immunopathogenesis. 1,9 Here we applied fluorescently labeled HBcAg as baits to ex vivo track HBcAg-specific B cells in blood samples of a wellcharacterized cohort of patients with CHB. We also examined functional differences in B cell ELISPOT assays.…”
Section: Discussionmentioning
confidence: 99%
“…Serum and/or peripheral blood mononuclear cells (PBMCs) were obtained from patients with CHB (n = 152, Table 1) attending the outpatient clinic of the Erasmus Medical Center, Rotterdam, the Netherlands or the Antwerp University Hospital, Antwerp, Belgium and categorized into 4 clinical HBV phases: immune tolerant (IT) or "HBeAg-positive chronic infection" -HBeAg+, HBeAb-, repetitive normal ALT (<upper limit of normal [ULN]); immune active (IA) or "HBeAg-positive chronic hepatitis" -HBeAg+, repetitive or intermittent high ALT (>ULN); inactive carrier (IC) or "HBeAg-negative chronic infection" -HBeAg-, HBeAb+, low ALT, HBV DNA <20,000 IU/ml; HBeAg-hepatitis (ENEG) or "HBeAg-negative chronic hepatitis" -HBeAg-, HBeAb+, repetitive or intermittent high ALT (>ULN). Categorization was performed as previously described 1,9,11 with minor modifications: i) no restrictions regarding the level of liver fibrosis, although most patients had < − F2 fibrosis; ii) cohorts of HBsAg-vaccinated healthy controls (HCs, n = 23) and virally suppressed nucleos(t) ide analogue (NUC)-treated patients with CHB (n = 34) were included; iii) For some IC patients intermittent ALT < − 2 ULN was allowed if there was documented liver steatosis without histological steatohepatitis and no other signs of liver disease. 12 ALT levels of IC patients remained significantly lower compared to ENEG and IA patients (Table 1; p <0.001).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…So far published studies assessing the clinical consequences of NA treatment stop after HBeAg seroconversion mainly focus on Asian patients . However, it is well appreciated that the host's ethnicity influences HBV's natural history and immune responses . Asian patients show, for example, lower spontaneous or treatment‐induced HBsAg seroclearance rates, and have higher HBV relapse rates in HBeAg‐negative patients after treatment cessation .…”
Section: Introductionmentioning
confidence: 99%
“…12 However, it is well appreciated that the host's ethnicity influences HBV's natural history and immune responses. 4,15 Asian patients show, for example, lower spontaneous or treatmentinduced HBsAg seroclearance rates, and have higher HBV relapse rates in HBeAg-negative patients after treatment cessation. 16 Clinical hepatocellular carcinoma risk scores developed in Asian cohorts seem to be unreliable in Caucasian and especially African patients, the latter developing hepatocellular carcinoma at much younger ages.…”
Section: Introductionmentioning
confidence: 99%